The Role of Accounting Lecturers in Understanding Financial Accounting Courses for Diploma 3 Accounting Students at the Medan State Polytechnic - Adhi Surya Harahap (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the role of accounting lecturers in helping Diploma 3 Accounting students at Politeknik Negeri Medan to understand Financial Accounting courses. The research focuses on the various teaching methods and strategies applied by the lecturers and how these influence students' understanding. Data was collected through interviews with lecturers and questionnaires distributed to students. The results show that practical teaching approaches, including case studies and feedback, significantly enhance students' comprehension of the course materials. Lecturers play a crucial role not only as educators but also as facilitators who bridge the gap between theory and practice in financial accounting. The study concludes that lecturers should continue to innovate their teaching methods to improve learning outcomes.